Methodology for Assessing Financial Results of Implementation of Energy Innovations Depending on their Progressiveness - Dudin, Mihail Nikolaevich; Zasko, Vadim Nikolaevich; Dontsova, Olesya Igorevna; Osokina, Irina Valentinovna (International Journal of Energy Economics and Policy, 2022)
The purpose of this article is to develop a methodology that can be used for an objective assessment of financial results and to support managerial decision-making regarding the implementation of energy innovations. The methodology is developed using an interdisciplinary approach and is based on the fuzzy logic theory and method, which allows converting expert judgments and qualitative assessments into final quantitative indicators with some degree of confidence. The methodology includes five input variables that form a fuzzy set "progressivity versus regressivity of energy innovations". The article considers the main criteria based on which an energy innovation can be classified as technologically progressive or regressive. The article demonstrates the efficiency of the developed methodology drawing on the example of two projects for the implementation of energy innovations. The data obtained have shown that one of the innovations can be considered conditionally technologically progressive only by 46%, while the second is certainly technologically progressive by 92%. The conducted correction of the basic financial results allows demonstrating that the implementation project of a conditionally technologically progressive innovation is not cost-effective and requires an increase in capital expenditures or a reduction in expected revenues since it requires a balanced assessment of the feasibility of implementing innovation.